Responsibilities of air carriers on international flights - Retno Sariwati (Faculty of Law, University of Merdeka Malang, 2022)
In international air transportation, it is sure to talk about the responsibility of the carrier, which cannot be separate from the discussion of international agreements, namely, in this case, the 1999 Montreal Convention, which contains the issue of the responsibility of international air carriers. This study aims to determine the guilt of air carriers on international flights to passengers, shippers, and third parties in the event of an aircraft accident. The approach method used in this research is normative juridical (legal research), using legal materials as the primary material. The carrier's responsibility is based on the absolute principle; the page is responsible but is still limited by the limitation principle (the carrier's responsibility is limited to a certain amount). The airline's responsibility is based on the presumption and limitation of liability for consignments and baggage. The carrier is always considered responsible until the airline can prove that it is not guilty of the event that caused the loss. The carrier's responsibility for baggage should be absolute because, by the time the passenger brings the bags, it has passed several checks that have confirmed that the goods in the luggage are not problematic.How to cite item:Â Sariwati, R. (2022). Responsibilities of air carriers on international flights.Â Jurnal Cakrawala Hukum, 13(2), 194-201. DOI:https://doi.org/10.26905/idjch.v13i2.7963.